Choosing the Future for American Juvenile Justice - Zimring, Franklin E.; Tanenhaus, David Spinoza (Book collections on Project MUSE., 2014)
This is a hopeful but complicated era for those with ambitions to reform the juvenile courts and youth-serving public institutions in the United States. As advocates plea for major reforms, many fear the public backlash in making dramatic changes. Choosing the Future for American Juvenile Justice provides a look at the recent trends in juvenile justice as well as suggestions for reforms and policy changes in the future. Should youth be treated as adults when they break the law? How can youth be deterred from crime? What factors should be considered in how youth are punished?What role should.